AWARENESS, ATTITUDES, SKILLS, AND OPEN EDUCATIONAL RESOURCES USAGE AMONG OPEN AND DISTANCE LEARNERS - AMBROSE, Eromosele Smart; Blessings Amina; Ogbomo, Esoswo Francisca (Indonesian Journal of Library and Information Science, 2024)
Open Educational Resources (OER) are adjudged to be of tremendous benefit to open and distance learners due to the nature of their academic programs. However, the level to which they will use these resources will be determined by certain factors. Thus, this study examined the influence of awareness, attitudes, and skills on the usage of OER by postgraduate students at the National Open University of Nigeria (NOUN), South-South, Nigeria. Four hypotheses were generated and tested to guide the study. On a population of 2,119 postgraduate students, the study used a descriptive survey design of the correlational type. Fifteen percent of the population (318) was sampled for the study. A questionnaire was used to elicit data from the respondents, and upon administration, a 95% response rate was achieved. The data were analyzed using descriptive statistics (for the demographics) and inferential statistics (for the hypotheses). The results revealed that the independent variables of awareness, attitude, and skills all had moderate individual and joint influence on the usage of OER among open and distance learners. The study concluded that, to stimulate use of OER among postgraduate students, their awareness, attitude, and skills would have to be positively triggered. Consequently, recommendations were made.